Mysterious odd radio circle near the large magellanic cloud – an intergalactic supernova remnant?. Issue 1 (4th February 2022) - Filipović, Miroslav D; Payne, J L; Alsaberi, R Z E; Norris, R P; Macgregor, P J; Rudnick, L; Koribalski, B S; Leahy, D; Ducci, L; Kothes, R; Andernach, H; Barnes, L; et al.
ABSTRACT: We report the discovery of J0624–6948, a low-surface brightness radio ring, lying between the Galactic Plane and the large magellanic cloud (LMC). It was first detected at 888 MHz with the Australian Square Kilometre Array Pathfinder (ASKAP), and with a diameter of ∼196 arcsec. This source has phenomenological similarities to odd radio circles (ORCs). Significant differences to the known ORCs – a flatter radio spectral index, the lack of a prominent central galaxy as a possible host, and larger apparent size – suggest that J0624–6948 may be a different type of object. We argue that the most plausible explanation for J0624–6948 is an intergalactic supernova remnant due to a star that resided in the LMC outskirts that had undergone a single-degenerate type Ia supernova, and we are seeing its remnant expand into a rarefied, intergalactic environment. We also examine if a massive star or a white dwarf binary ejected from either galaxy could be the supernova progenitor. Finally, we consider several other hypotheses for the nature of the object, including the jets of an active galactic nucleus (30Dor) or the remnant of a nearby stellar super-flare.